2014
DOI: 10.1016/j.jad.2014.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological impairments in panic disorder: A systematic review

Abstract: There is limited evidence of specific neuropsychological impairments in participants with PD. Impairments in short term memory warrant further investigation to establish their relevance to clinical practice. Larger sample sizes and appropriate statistical adjustment for multiple comparisons in future studies is highly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…Higher levels of IL-1β and IL-6 in panic disorder patients may interfere with differentiation and activation of naïve CD8+ T, possibly reducing inflammation. Links between inflammatory response and presentation of neurodegeneration and neuropsychological performance [ 41 , 42 ] are consistent both with our results and the limited evidence for neuropsychological impairments in PD patients [ 43 ]. Although cause and consequence remain unclear, additional research into immune modulation for PD cases could have value for patients and provide options to treating physicians.…”
Section: Discussionsupporting
confidence: 91%
“…Higher levels of IL-1β and IL-6 in panic disorder patients may interfere with differentiation and activation of naïve CD8+ T, possibly reducing inflammation. Links between inflammatory response and presentation of neurodegeneration and neuropsychological performance [ 41 , 42 ] are consistent both with our results and the limited evidence for neuropsychological impairments in PD patients [ 43 ]. Although cause and consequence remain unclear, additional research into immune modulation for PD cases could have value for patients and provide options to treating physicians.…”
Section: Discussionsupporting
confidence: 91%
“…In a review of the literature investigating the neuropsychological disturbances PDA, limited support for impairment in short-term memory among individuals with PD was found in some but not all studies. Moreover, the studies did find some evidence for impairment in other areas of cognitive functioning, including executive function, long-term memory, visuospatial or perceptual abilities and working memory (O’Sullivan & Newman 2014). The review included 14 studies (total 439 patients, 510 healthy controls), the majority of which had average to high methodological quality.…”
Section: Neurocognitionmentioning
confidence: 99%
“…A recent systematic review did not support the presence of cognitive functioning deficits in PD though there was marginal evidence of short-term memory deficits among PD individuals[86]; these findings reflected those of Gladsjo et al[87] who found no group differences between PD subjects and healthy controls on visuospatial, learning, memory, psychomotor speed, and attention tasks.…”
Section: Anxiety Disordersmentioning
confidence: 86%